Rainfall - Runoff Modeling - A Case Study of lb River Basin - Sharma, K.N.; sharma, S.D. (Journal of Soil and Water Conservation, 2022)
The Study for development of rainfall fall-runoff models was conducted on river lb catchments Rainfall recorded at different locations in the catchment and runoff recorded at Sundergarh and Deogaon gauging sites were used for the study. `Math Card" software programme was used for determining best fit regression models. Daily data of average rainfall and runoff of the two sub- catchments for monsoon season for the period of 1978 to 1993 were put in the programme. Data were arranged in different forms i.e. daily average for entire period. daily average for sub periods, daily average of different sub-seasons yearly sub-season and annual. Acceptable models with high degree of correlation coefficient were found for yearly sub-seasonal data and annual data.